2022
DOI: 10.3390/metabo12100997
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Potential Serum Biomarkers with Pro-Inflammatory and DNA Damage Activities in Ulcerative Colitis: A Comprehensive Untargeted Metabolomic Study

Abstract: Ulcerative colitis is a type of non-specific inflammatory bowel disease with unclear etiology. It is considered a progressive disease with risks of bowel motility disorders, anorectal dysfunction, and even colorectal cancer. Commonly used diagnostic markers have poor specificity and cannot predict the development of ulcerative colitis. In this study, 77 serum samples (31 patients, 46 healthy controls) were analyzed using high performance liquid chromatography-quadrupole time-of-flight mass spectrometry and 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The findings here reported revealed among the medwakh smoker group an increased level of metabolites linked with inflammatory mechanism, such as pyroglutamic acid 23 , 24 , deoxyguanosine 25 and anserine 26 . In order to investigate futher an eventual association of metwakh smoking and inflammation, we decided to measure CRP, a widely known clinical indicator of inflammatory conditions 27 , 28 .…”
Section: Resultssupporting
confidence: 56%
“…The findings here reported revealed among the medwakh smoker group an increased level of metabolites linked with inflammatory mechanism, such as pyroglutamic acid 23 , 24 , deoxyguanosine 25 and anserine 26 . In order to investigate futher an eventual association of metwakh smoking and inflammation, we decided to measure CRP, a widely known clinical indicator of inflammatory conditions 27 , 28 .…”
Section: Resultssupporting
confidence: 56%
“…Mangiferin, a natural flavonoid compound with anti-inflammatory and anti-oxidant properties, and Evodiamine, a supplement with anti-tumor and anti-inflammatory pharmacological effects, were both up-regulated in the S-LoAI/HiII (low adaptive/high innate immunity) subtype. Pyroglutamic acid, a cancer biomarker and previously shown as being elevated in the serum of ulcerative colitis patients, was found up-regulated in the S-LoII (low innate immunity) subtype [53]. Further, the up-regulated metabolite Pyroglutamic acid was found to be significantly altered in influenza high-risk groups in a recent study [10].…”
Section: Resultsmentioning
confidence: 97%
“…80 Relationship between coffee/CAF consumption and colonic inflammation has been summarized in Table 1. [81][82][83][84][85][86] An association between coffee/CAF consumption and colonic tumorigenesis has been summarized in Table 2. [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] Within this table, about 84% of studies showed the beneficial effects of coffee/CAF intake for CRC development among the various type of studies.…”
Section: Pros and Cons Of Coffee/caf Intake On The Effect Of Inflamma...mentioning
confidence: 99%
“…Although coffee/CAF intake seems to reduce the inflammatory responses in the colon [ 9 , 74 , 79 ], recent 2 reports suggest that CAF consumption is positively associated with the prevalence of CD or UC [ 75 ] as well as irritable bowel syndrome [ 80 ]. Relationship between coffee/CAF consumption and colonic inflammation has been summarized in Table 1 [ 81 - 86 ].…”
Section: Pros and Cons Of Coffee/caf Intake On The Effect Of Inflamma...mentioning
confidence: 99%